The value of bibliography in qualitative health research - Carmen de la Cuesta Benjumea (Universidad de Alicante, 2017)
Bibliography in qualitative research must come to live. The person that reads interprets. He/she is a reflective person that while reading is constructing a world view; creates analytic paths and theoretical avenues. Hence the value of bibliography does not rest on itself but on the act of reading. When to read and how to do it is going to be as important as what to read. There are three occasions, in which bibliography enters in a research study with a different objective on each occasion. At the beginning when the study is introduced, during the study when the analysis is developed and at the end when results are rendered. This paper explores the value of bibliography on each of them